Pedagogical in the Methodology of Music Education Formation of Knowledge - kizi, Rustamjonova Dilkhavas Ravshvnbek (Researchparks Publishing, 2023)
This scientific article is dedicated to the formation of the personality of a pedagogue, the problems of acquiring knowledge, skills and abilities necessary for the implementation of pedagogical activities.